Perilaku Pemilih pada Pilkades Tahun 2019 Perspektif Fiqh Siyasah di Desa Jubung Kecamatan Sukorambi Kabupaten Jember - Ahmad Nuris Sholeh; Robitul Firdaus (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2021)
The people of Jubung Village also became voters in the simultaneous Pilkades in 2019. The tendency of the community to choose one candidate, has been formed from environmental factors or the surrounding community. In addition, voter behavior is also influenced by many factors, such as religious factors, certain groups and political policy issues. Although on the other hand, doctrinally Islam does not teach the procedure for choosing a leader, but Islam teaches the criteria for a good leader. This study uses a qualitative descriptive method with a case study strategy. Sources of data used are informants, archival documents and places and events. In this study there are findings including; The behavior of voters in Jubung Village generally has a traditional type and a small portion has a rational and critical type. The preferences of voters in Jubung Village are generally motivated by sociological factors and the image of each candidate. The leader's criteria for the voting community in making their choice in the 2019 Pilkades have been in accordance with the siyasa syar`iyah, namely based on the shari'a laws.